Midinfrared intersubband absorption on AlGaN/GaN-based high-electron-mobility transistors - Hofstetter, Daniel; Diehl, Laurent; Faist, Jérôme; Schaff, William J.; Hwang, Jeff; Eastman, Lester F.; Zellweger, Christoph (My University, 2002)
Intersubband absorption measurements on two nominally undoped AlGaN/GaN-based high-electron-mobility transistors with different Al compositions in the barrier layer are presented. The first transistor with a barrier consisting of Al0.6Ga0.4N showed an absorption peak at 247 meV (1973 cm–1) with a full width at half maximum (FWHM) of 126 meV, while the second device utilizing an Al0.8Ga0.2N barrier had its peak at 306 meV (2447 cm–1) with a FWHM of 86 meV. Self-consistently computed potentials and intersubband transition energies showed good agreement with the experimental findings, and therefore confirmed previously published values for the internal piezoelectric field in such structures.